Hotade skånska arter : ett gestaltningsförslag till Botaniska trädgården vid Lunds Universitet - Holmberg, Hanna (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
The goal has been to come up with a design proposal for Lund Botanical Garden. Botan, which the garden is called in daily speech, is part of a project together with, Länsstyrelsen Skåne on native endangered species. One of their tasks in the project is to showcase the plant material and inform the public about the project and the plants. It is for the part of the garden which is meant to contain this exhibition the design proposal in this paper is made for.